Willingness to communicate among Korean learners of English - Edwards, Peter A. (2006)
Many Koreans not only feel strongly motivated to study English but they also enthusiastically pursue learning the language, and yet when real contact situations arise in which English could be used, many Koreans remain unwilling to do so. Better understanding this phenomenon could benefit not only Koreans but also other groups of people who see great value in learning a language but undercut their own efforts by avoiding opportunities to use it. Through a series of interviews leading to a large quantitative study, this research investigates some underlying factors which influence Korean learners' decision over whether to use English in a particular situation. The main findings suggest that the quality and quantity of previous contact with the non-Korean world, for example through travel and friendship, along with the presence and relative status of other Koreans at the communication event, significantly influence language use. These results generally support the theories of the Contact Hypothesis (CH) and Willingness to Communicate (WTC). These disparate theories, together in the Korean context, suggest a need for greater focus on L2 friendship and L 1 status issues in language learning.